Coating in the arc discharges with plasma flow filtration - Gasilin, V. V.; Zavaleyev, V.A.; Nezovibat’ko, Yu. N.; Shvets, O.M.; Taran, V.S.; Skorina, E.V. (Вопросы атомной науки и техники, 2006)
Experimental results of coating deposition with application of an “open architecture” filter to reduce the dropwise component in the discharge [1,2] are presented in this paper. The filter is located in a separate chamber conjugate with the presented system. A curvilinear (with an angle 90°) solenoid creating a transporting magnetic field [3] is used as the “open architecture” filter. Performing probe measurements of the ion saturation current dependences on the current of focussing coil, pressure of inert gas (argon) and reactionary gas (nitrogen). The measurement results of substrate temperature, deposition rate of coating.